2023
DOI: 10.1038/s41467-023-35897-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupled induction of prophage and virulence factors during tick transmission of the Lyme disease spirochete

Abstract: The alternative sigma factor RpoS plays a central role in the critical host-adaptive response of the Lyme disease spirochete, Borrelia burgdorferi. We previously identified bbd18 as a negative regulator of RpoS but could not inactivate bbd18 in wild-type spirochetes. In the current study we employed an inducible bbd18 gene to demonstrate the essential nature of BBD18 for viability of wild-type spirochetes in vitro and at a unique point in vivo. Transcriptomic analyses of BBD18-depleted cells demonstrated globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 108 publications
2
24
0
Order By: Relevance
“…We hypothesize that genetic transfer and recombination occur when Borrelia spirochetes are within ticks. A recent study of borrelia bacteriophage induction supports that hypothesis (44).…”
Section: Horizontal Transfer and Recombinationmentioning
confidence: 75%
See 1 more Smart Citation
“…We hypothesize that genetic transfer and recombination occur when Borrelia spirochetes are within ticks. A recent study of borrelia bacteriophage induction supports that hypothesis (44).…”
Section: Horizontal Transfer and Recombinationmentioning
confidence: 75%
“…Intriguingly, even though MNNG is a mutagen, B. burgdorferi lacks an SOS system (14), so the means through which this chemical induces bacteriophage production is not yet known. It was recently reported that dysregulation of the RpoS alternative sigma factor led to production of fBB1 bacteriophage particles (44). Characterizing the mechanism that controls the lysogenic vs. lytic phases of fBB1 will undoubtedly yield important insights on the breadth of bacteriophage biology.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli , we observed some minor effects on RpoS levels when flgV was expressed; however, these outcomes could be indirect. In B. burgdorferi , RpoS is a cornerstone for responding to environmental changes during the enzootic cycle, and therefore, its regulation must be tightly controlled (Wachter et al ., 2023). It was previously proposed that FlgV post-transcriptionally regulates rpoS because it was reported that deletion of flgV led to higher levels of rpoS mRNA, but lower levels of RpoS protein and lower levels the RpoS-regulated ospC mRNA (Lybecker et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In natural populations, genetic variation in outer membrane lipoprotein alleles is associated with species-level adaptations [6,[8][9][10] and variation in outer membrane lipoprotein alleles across the genospecies is driven primarily by horizontal gene transfer [5,[11][12][13][14][15][16][17][18][19][20][21]. However, the mechanism(s) by which heterologous B. burgdorferi strains exchange genetic material are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…A key factor in the ability of B. burgdorferi to transmit from its tick vector to a vertebrate host is the differential expression of several outer membrane lipoproteins that assist B. burgdorferi in evading both vector and host immune responses [7]. As such, a large fraction of the B. burgdorferi genome encodes outer membrane lipoproteins, mostly carried on the plasmids [6, 8, 9].…”
Section: Introductionmentioning
confidence: 99%